PERPUSTAKAAN DIGITAL DALAM PUBLIKASI JURNAL INTERNASIONAL: SEBUAH ANALISIS TEMATIK DI GOOGLE SCHOLAR - Nafisah, Elok; Winoto, Yunus (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
Digital library is not a new topic in the library world. Various studies on digital libraries have also been carried out and have resulted in publications in various journals. The purpose of this research is to find out: (1) the development of international publications about digital libraries in 2017-2021, (2) core journals in international publications about digital libraries, (3) the development of international publications with the keyword digital library, and (4) development of international publications on digital libraries by author. The method used in this study is a qualitative research method with data acquisition through library research and bibliometric analysis using Publish or Perish and VOSviewer on the topic of digital libraries. The results showed that the development of research on the topic of digital libraries in the period 2017-2021 experienced fluctuating growth but did not change so much every year. The highest publication was in 2017 with 47 articles and the lowest in 2018 with 30 articles. Most publications were carried out by the Journal of Librarianship and Information Science 4 times. The topic of research on digital libraries is still a lot about information, models, university and impact. Researchers still rarely collaborate in writing scientific papers about digital libraries.Keywords: digital library, thematic analysis, bibliometrics, publish or perish, VOSviewer, google scholarsABSTRAKPerpustakaan digital bukanlah suatu topik yang asing lagi dalam dunia perpustakaan. Berbagai penelitian tentang perpustakaan digital pun sudah banyak dilakukan dan menghasilkan publikasi di berbagai jurnal. Tujuan dari penelitian ini adalah untuk mengetahui: (1) perkembangan publikasi internasional tentang perpustakaan digital pada tahun 2017 – 2021, (2) jurnal inti dalam publikasi internasional tentang perpustakaan digital, (3) perkembangan publikasi internasional dengan kata kunci perpustakaan digital, serta (4) perkembangan publikasi internasional tentang perpustakaan digital berdasarkan penulis. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan perolehan data melalui studi pustaka dan analisis bibliometrik menggunakan Publish or Perish dan VOSviewer pada topik perpustakaan digital. Hasil penelitian menunjukkan bahwa perkembnagan penelitian tentang topik perpustakaan digital pada rentang tahun 2017 – 2021 mengalami pertumbukan yang fluktuatif namun tidak berubah begitu besar tiap tahunnya. Publikasi tertinggi yaitu pada tahun 2017 sebanyak 47 artikel dan terendah pada tahun 2018 sebanyak 30 artikel. Publikasi terbanyak dilakukan oleh Journal of Librarianship and Information Science sebanyak 4 kali. Topik penelitian tentang digital library masih banyak tentang information, model, university dan impact. Peneliti masih jarang melakukan kerjasama dalam penulisan karya ilmiah tentang digital library.